Treatment with THI, an inhibitor of sphingosine-1-phosphate lyase, modulates glycosphingolipid metabolism and results therapeutically effective in experimental models of Huntington’s disease - Pepe, Giuseppe; Capocci, Luca; Marracino, Federico; Realini, Natalia; Lenzi, Paola; Martinello, Katiuscia; Bovier, Tiziana Francesca; Bichell, Terry Jo; Scarselli, Pamela; Di Cicco, Clotilde; Bowman, Aaron B.; Digilio, Filomena A.; et al. (Molecular therapy, 2023)
Huntington’s disease (HD) is a fatal neurodegenerative disorder with no effective cure currently available. Over the past few years our research has shown that alterations in sphingolipid metabolism represent a critical determinant in HD pathogenesis. In particular, aberrant metabolism of sphingosine-1-phosphate (S1P) has been reported in multiple disease settings, including human postmortem brains from HD patients. In this study, we investigate the potential therapeutic effect of the inhibition of S1P degradative enzyme SGPL1, by the chronic administration of the 2-acetyl-5-tetrahydroxybutyl imidazole (THI) inhibitor. We show that THI mitigated motor dysfunctions in both mouse and fly models of HD. The compound evoked the activation of pro-survival pathways, normalized levels of brain-derived neurotrophic factor, preserved white matter integrity, and stimulated synaptic functions in HD mice. Metabolically, THI restored normal levels of hexosylceramides and stimulated the autophagic and lysosomal machinery, facilitating the reduction of nuclear inclusions of both wild-type and mutant huntingtin proteins.
Online verfügbar 16. September 2022, Artikelversion 4. Januar 2023
Gesehen am 06.06.2023